Protective effects of asiaticoside on renal ischemia reperfusion injury in vivo and in vitro. Issue 4 (1st April 2022) - Tang, Shengjie; Xie, Xiangcheng; Wang, Ming; Yang, Lili; Wei, Wei
ABSTRACT: Ischemia/reperfusion injury (I/R) is the main causes of acute kidney injury (AKI), which is a global health concern. Evidence suggests that asiaticoside plays vital roles on anti-inflammatory and, anti-kidney fibrosis effects, and promotes tissue repair. However, the effects of asiaticoside on AKI caused by ischemia-reperfusion have not been well defined. Herein, we explored the protective effect of asiaticoside on renal ischemia-reperfusion injury (IRI) using in vivo and in vitro studies, and elucidated the potential mechanism of asiaticoside-mediated repair. Results showed that asiaticoside attenuated the levels of blood urea nitrogen (BUN) and serum creatinine (Scr) in the IRI model. Meanwhile, asiaticoside reduced the secretion of IL-6, IL-1β and TNF-α, but increased IL-10 secretion in a dose-dependent manner. Treating Raw264.7 cells with lipopolysaccharide (LPS) induced an inflammatory response, but the LPS-induced effects were attenuated after administering asiaticoside. Furthermore, asiaticoside significantly inhibited the expression of inducible Nitric Oxide Synthase (iNOS) and promoted the expression of Arginase1 induced by LPS, which are the polarization marker proteins. In conclusion, this study shows that asiaticoside possesses protective action in AKI after ischemia-reperfusion, due to the inhibition of inflammatory mediators and promoting transformation of macrophages from M1 type to M2 type. Graphical Abstract: uf0001